Bioresorbable coronary stent for the treatment of complex coronary lesions: Data from an all-comer registry. (1st March 2017) - Cuculo, Andrea; Ruggiero, Antonio; Centola, Antonio; Campanale, Giulio; Passero, Tommaso; Gaglione, Antonio; Di Biase, Matteo; Brunetti, Natale Daniele
Abstract: Background: The study aimed to report the results from an all-comers registry of patients undergoing coronary angioplasty and treated with bioresorbable vascular scaffold (BVS). Methods: Fifty-five consecutive patients with type B/C coronary lesions according to the AHA classification and treated with BVS were enrolled in the study. The clinical and procedural characteristics of enrolled patients were recorded. Fifty-five consecutive subjects with coronary lesions type B/C treated with everolimus eluting stent (EES) were used as control group. Results: The incidence of adverse events was not statistically significant comparing subjects treated with BVS with those treated with EES. Non significant differences were also found in the follow-up considering the presence of diabetes, multivessel disease, use of more than one stent at the same time, diagnosis (STEMI vs UA/NSTEMI), use of coronary stents in overlapping. The differences were significant considering the type of lesion (Log-Rank p  < 0.05), stenoses treated in correspondence of a coronary bifurcation ( p  < 0.05), the SYNTAX score (cut off 22) ( p  < 0.001); after multivariable correction for age and gender, however, differences remained significant only for SYNTAX score. Conclusions: The use of BVS in an all-comers registry of patients undergoing coronary angioplasty on complex coronary lesions is associated with a safety profile comparable to that obtained with EES; the use of BVS in particular conditions, such as very high SYNTAX score, should be further assessed.